A Novel Salmonella Periplasmic Protein Controlling Cell Wall Homeostasis and Virulence - Cestero, Juan J.; Castanheira, Sónia; Pucciarelli, M. Graciela; García-del Portillo, Francisco (Frontiers in Microbiology, 2021)
Horizontal gene transfer has shaped the evolution of Salmonella enterica as pathogen. Some functions acquired by this mechanism include enzymes involved in peptidoglycan (PG) synthesis and remodeling. Here, we report a novel serovar Typhimurium protein that is absent in non-pathogenic bacteria and bears a LprI functional domain, first reported in a Mycobacterium tuberculosis lipoprotein conferring lysozyme resistance. Based on the presence of such domain, we hypothesized a role of this S. Typhimurium protein in PG metabolism. This protein, which we named ScwA for Salmonellacell wall-related regulator-A, controls positively the levels of the murein lytic transglycosylase MltD. In addition, the levels of other enzymes that cleave bonds in the PG lattice were affected in a mutant lacking ScwA, including a soluble lytic tranglycosylase (Slt), the amidase AmiC, and a few endo- and carboxypeptidases (NlpC, PBP4, and AmpH). The scwA gene has lower G+C content than the genomic average (43.1 vs. 52.2%), supporting acquisition by horizontal transfer. ScwA is located in the periplasm, stabilized by two disulfide bridges, produced preferentially in stationary phase and down-regulated following entry of the pathogen into eukaryotic cells. ScwA deficiency, however, results in a hypervirulent phenotype in the murine typhoid model. Based on these findings, we conclude that ScwA may be exploited by S. Typhimurium to ensure cell envelope homeostasis along the infection and to prevent host overt damage. This role could be accomplished by controlling the production or stability of a reduced number of peptidoglycan hydrolases whose activities result in the release of PG fragments.